A person-centred approach to understanding cultures of assessment. Issue 8 (17th November 2018) - Skidmore, Susan T.; Hsu, Hsien-Yuan; Fuller, Matthew
Abstract: The purpose of the present study was to investigate how faculty members coalesce into distinguishable groups in terms of their perceived cultures of assessment at their respective institutions. To date, although researchers have posited the existence of various cultures of assessment, no study to our knowledge has empirically demonstrated the presence of these unobserved (latent) cultures analytically. Accordingly, a latent profile analysis was conducted using Mplus to identify these unobserved groups based on faculty ( n = 1148) members' responses to 12 items (6-point Likert scale) selected from the 2014 Faculty Survey of Assessment Culture . The resulting 4-class solution, including a previously unidentified group, was confirmed by the Lo-Mendell-Rubin Adjusted Likelihood Ratio Test: Culture of Student Learning ( n = 502); Evolving Student Learning Culture ( n = 398); Culture of Compliance ( n = 168); and Culture of Fear ( n = 80). Characteristics of each class are described and the prevalence of each class by type of degree granting institution and primary discipline is provided.